Efficacy of alpha-cypermethrin and thiamethoxam against Trogoderma granarium Everts (Coleoptera: Dermestidae) and Tenebrio molitor L. (Coleoptera: Tenebrionidae) on concrete. (May 2015) - Athanassiou, Christos G.; Kavallieratos, Nickolas G.; Boukouvala, Maria C.; Mavroforos, Marios E.; Kontodimas, Demetrius C.
Abstract: Laboratory bioassays were conducted to evaluate alpha-cypermethrin and thiamethoxam for the control of adults, small larvae and large larvae of the khapra beetle Trogoderma granarium, and the yellow mealworm beetle Tenebrio molitor, on concrete. Factors such as dose (0.025 and 0.1 mg alpha-cypermethrin or thiamethoxam/cm 2 ), exposure interval (1, 3 and 7 d), and formulation (alpha-cypermethrin SC and thiamethoxam WG) were evaluated. Apart from immediate assessment at end of exposure, an assessment of delayed mortality was performed with the survivors of the 7-d exposure by removing them from the treated substrate and keeping them on untreated surfaces for 7 more days. After the 7-d exposure, more T. granarium adults were dead on dishes treated with alpha-cypermethrin than with thiamethoxam. Small larvae were generally less susceptible than adults. After 7 d, small larval mortality reached 64.4% for alpha-cypermethrin, while for thiamethoxam it was <6%. Large T. granarium larvae were more tolerant than the small ones. Delayed mortality of T. granarium adults was generally high for both insecticides and doses, and ranged between 43.3 and 63.3% of those that were still alive immediately after the 7-d treatment. For both larval categories, delayed mortality was higher for larvae that had been previously exposed to alpha-cypermethrin, than with thiamethoxam. For T. molitor, after the 7-d exposure, significantly more adults were dead on dishes treated with alpha-cypermethrin than with thiamethoxam. For small larvae mortality was 38.9% at the lowest thiamethoxam dose, but in the other cases ranged between 88.9 and 95.6%. In the case of large larvae, the overall mortality was low in all tested combinations. Regarding delayed mortality of this species, it remained at low levels, for both adults and small larvae. Our results indicate that T. molitor was more susceptible than T. granarium in both insecticides tested, but alpha-cypermethrin was more effective than thiamethoxam. Highlights: Tenebrio molitor was more susceptible than Trogoderma granarium in all combinations tested. alpha-Cypermethrin was more effective than thiamethoxam for control of T. molitor. Adults were generally more susceptible than larvae. Large larvae were more tolerant to both insecticides than small larvae.